(untitled) (International Journal of Scientific Trends, 2026)
The article examines the study of works created by thinkers of the Islamic world by Eastern and Western scholars. Muslim philosophy is multifaceted, and the approaches of Western and Eastern researchers are also different. It is no secret that the rational view is studied more by Western scholars, and in general, philosophical analysis is characteristic of the West. In the Muslim world, there are also many researchers who conduct research based on Western methodology, which indicates the existence of a somewhat one-sided approach. One of the complex issues here is the rational analysis of theological views. In this regard, the phenomena of Al-Farabi, Ibn Sina, Ibn Rushd, and Imam Ghazali are unparalleled. The main issues in Muslim philosophy are reflected in the works of these scholars. Although Western research on Muslim philosophy has been significant to date, the work of Iranian, Turkish, Egyptian, and Indian scholars is also commendable. New approaches to the study of Eastern Muslim philosophy will make a worthy contribution to the improvement of the disciplines of religious studies, Islamic studies, and philosophy of religion in our homeland.